Quality Test of Extemporaneously Prepared Tramadol and Paracetamol Capsules Combination Derived From a Private Hospital in Semarang - Paulus Unggul Wikan Prabandono; Michael Raharja Gani; Sri Hartati Yuliani (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2021)
Tramadol and paracetamol are analgesic drugs that are often combined and made in the form of extemporaneously prepared capsules dosage form to treat moderate to severe pain management. This study aims to determine the quality of prescribed medication of extemporaneously prepared tramadol and paracetamol capsules combination taken from a private hospital in Semarang covering weight uniformity, moisture content, disintegration, and content uniformity. This type of research is a descriptive observational cross-sectional design. Samples were taken using simple random sampling at a pharmaceutical installation in a private hospital in Semarang. The observation result from four types of testing was compared against the standard values of each test’s parameter listed in the Indonesian Pharmacopoeia V. The results are, samples meet the weight uniformity test with an acceptance value of 7.34%; meet the moisture content test with an average moisture content of 2.647% for the first day and 3.04% for the seventh day; meet the disintegration test with a breakdown time of fewer than 15 minutes; and did not meet the uniformity test with acceptance value of 34.06% for paracetamol and 34.30% for tramadol. It can be concluded that the prescribed medication of extemporaneously prepared capsule samples derived from a private hospital in Semarang can fulfill the standard values listed in the Indonesian Pharmacopoeia V except for the content uniformity test.